2019
DOI: 10.1126/science.aat6280
|View full text |Cite
|
Sign up to set email alerts
|

Commensal-specific T cell plasticity promotes rapid tissue adaptation to injury

Abstract: Barrier tissues are primary targets of environmental stressors and are home to the largest number of antigen-experienced lymphocytes in the body, including commensal-specific T cells. We found that skin-resident commensal-specific T cells harbor a paradoxical program characterized by a type 17 program associated with a poised type 2 state. Thus, in the context of injury and exposure to inflammatory mediators such as interleukin-18, these cells rapidly release type 2 cytokines, thereby acquiring contextual func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
226
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(239 citation statements)
references
References 57 publications
12
226
0
1
Order By: Relevance
“…Given the broad range of responses seen after TCR and cytokine mediated activation we speculated that functions of MAIT cells extended beyond conventional antimicrobial functions.The recent discovery of a skin-homing Tc17 subset in mouse responsive to commensal ligands has shed light on a unique form of adaptive immunity where antimicrobial functions and tissue repair are coupled within the same subset of unconventional T cells (Harrison et al, 2019;Linehan et al, 2018). These commensal-specific T cells elicited a tissue repair signature and accelerated wound closure, in addition to promoting protection to pathogens.…”
Section: Transcriptional Signatures Of Activated Mait Cells Predict Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the broad range of responses seen after TCR and cytokine mediated activation we speculated that functions of MAIT cells extended beyond conventional antimicrobial functions.The recent discovery of a skin-homing Tc17 subset in mouse responsive to commensal ligands has shed light on a unique form of adaptive immunity where antimicrobial functions and tissue repair are coupled within the same subset of unconventional T cells (Harrison et al, 2019;Linehan et al, 2018). These commensal-specific T cells elicited a tissue repair signature and accelerated wound closure, in addition to promoting protection to pathogens.…”
Section: Transcriptional Signatures Of Activated Mait Cells Predict Nmentioning
confidence: 99%
“…Notably although the magnitude of change seen in our experiments was greater in the cytokine-stimulated cells, the transcripts associated with TCR triggering alone provided a clear insight into potential function. We linked, using GSEA, the MAIT TCR-driven transcriptional profile with a tissue repair signature from a recent report on IL17+ innate like CD8+ T cells in a murine skin model (Linehan et al, 2018) (later confirmed in the gut (Harrison et al, 2019)). The tissue repair profile in the unconventional (H-2 M3restricted) mouse skin CD8+ T cells was shown to be linked to encounter with commensal microbes and to impact on cutaneous wound healing.…”
Section: Responses Following a Tcr Stimulation Of Mait Cells And Convmentioning
confidence: 99%
See 1 more Smart Citation
“…Facing the global problems of aging of populations and antibiotic overuse, it has become more difficult to treat skin diseases, and new treatment approaches are needed. [ 16–18 ] CAP can not only sterilize common pathogenic and antibiotic‐resistant Staphylococcus aureus and Escherichia coli bacteria without harming normal cells of the skin sample, [ 19 ] but also stimulate the proliferation of mammalian cells. [ 20 ] The multiple modes of action of CAP in skin treatment include killing the microbes, tissue stimulation, anti‐inflammatory, and anti‐itch property, which make CAP ideal for dermatological applications in the treatment of inflammatory diseases and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation and maintenance of circulating memory subsets are also dynamically controlled by a compendium of transcription factors, including: Id2 (Cannarile et al, 2006;Knell et al, 2013;Masson et al, 2013), T-bet (Joshi et al, 2007), Blimp1 (Kallies et al, 2009;Rutishauser et al, 2009) Zeb2 (Dominguez et al, 2015;Omilusik et al, 2015), and STAT4 (Mollo et al, 2014) that are critical for TEM, and Id3 (Ji et al, 2011;Yang et al, 2011), Eomes (Banerjee et al, 2010;Pearce et al, 2003), Bcl6 (Ichii et al, 2002), Foxo1 (Hess Michelini et al, 2013;Rao et al, 2012), Tcf1 (Jeannet et al, 2010;Zhou et al, 2010), Zeb1 (Guan et al, 2018), Bach2 (Roychoudhuri et al, 2016), and STAT3 (Cui et al, 2011) that support TCM differentiation. TRM heterogeneity has been alluded to in multiple non-lymphoid sites and infection models (Bergsbaken and Bevan, 2015;Bergsbaken et al, 2017;Boddupalli et al, 2016;Harrison et al, 2019;Kumar et al, 2018;Masopust and Soerens, 2019), and differing levels of CD69 and CD103 have been useful in studying TRM maturation. However it is unlikely these molecules capture the full spectrum of TRM heterogeneity, as TRM are often uniformly CD69 + CD103 + in certain non-lymphoid sites such as the skin and small intestine or predominantly CD103 lo as in the kidney, heart and brain (Casey et al, 2012;Ma et al, 2017;Mackay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%